Will Democratization Save the Climate? An Entropy-Balanced, Random Slope Study. Issue 2 (3rd April 2017) - Mayer, Adam
Abstract : Democratization might be instrumental in addressing climate change on a global scale but the effect of democracy on carbon dioxide emissions is unclear. Treadmill of production (TOP) theory implies that democracy may increase emissions as publics pressure governments for increased economic growth. On the other hand, theories aligned with a rational choice perspective and ecological modernization perspectives suggest that democracy will reduce emissions as autocratic leaders have little incentive to address environmental policy. In this article, we clarify the role of democracy in emissions by using data that disaggregate different characteristics of democracies. Using novel causal inference techniques and generalized linear models, we allow the effect of democratic characteristics to vary across countries. Results indicate that democracy tends to reduce emissions, but the effect is modest, and its intensity varies significantly across countries.